2009
DOI: 10.1021/la902135t
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Lysozyme Charge Ladders to Examine the Effects of Protein Surface Charge Distribution on Binding Affinity in Ion Exchange Systems

Abstract: A lysozyme library was employed to study the effects of protein surface modification on protein retention and to elucidate preferred protein binding orientations for cation exchange chromatography. Acetic anhydride was used as an acetylating agent to modify protein surface lysine residues. Partial acetylation of lysozyme resulted in the formation of a homologous set of modified proteins with varying charge densities and distribution. The resulting protein charge ladder was separated on a cation exchange column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…The retention mechanism of lysozyme in cation‐exchange chromatography has been thoroughly investigated. By using an artificial lysozyme protein charge ladder, Chung et al identified two binding regions, which consist of five arginines, two lysines, one histidine, and the N‐terminus . Our results for the number of amino acids involved in lysozyme binding to cation exchanger are in a good agreement with these findings.…”
Section: Resultssupporting
confidence: 88%
“…The retention mechanism of lysozyme in cation‐exchange chromatography has been thoroughly investigated. By using an artificial lysozyme protein charge ladder, Chung et al identified two binding regions, which consist of five arginines, two lysines, one histidine, and the N‐terminus . Our results for the number of amino acids involved in lysozyme binding to cation exchanger are in a good agreement with these findings.…”
Section: Resultssupporting
confidence: 88%
“…Proteins can interact with a chromatographic surface via a preferred binding face or through multiple binding sites and orientations (Chung et al, ). In order to evaluate the relative importance of the four proposed multimodal binding sites (I–IV) identified on the wild type as shown in Figure , we first designed and produced a set of Fab charge variants (Table , C1 − to C5 − ) with reduced positive EP in each site.…”
Section: Resultsmentioning
confidence: 99%
“…Protein charge ladders were generated by acylation of the lysine ɛ‐amino groups of either lysozyme ( r p = 2 nm, 14.3 kDa, pI = 11) or α‐lactalbumin ( r p = 2 nm, 14.2 kDa, pI = 4.6) using acetic anhydride (Sigma 242845) following the procedure described by Chung et al (Figure ). The acylation reaction converts the protonatable amino group into a neutral amide, thereby reducing the number of positive charge groups on the protein.…”
Section: Methodsmentioning
confidence: 99%